Maternal knowledge and practice of safe infant sleep position in South Ethiopia: Implications for preventing sleep-related infant deaths - Tamene Demissie Lachore; Tamirat Toma Bekele; Alemayehu Beharu Tekle; Nega Degefa; Genet Assefa (PLoS ONE, 2026)
Background Safe infant sleep position practice is crucial for infants from birth to 12 months of age. One of the most important interventions in infancy is choosing the right sleeping position for the baby. The unsafe position of the child while sleeping is associated with sudden infant death Syndrome. However, little is known about the safe infant sleep position practice in Ethiopia. Therefore, this study aimed to assess safe infant sleep position practices among mothers attending child health care services in the Wolaita Zone public hospitals, South Ethiopia, 2024. Methods The study included 569 mothers with infants attending child health care services in public hospitals in the Wolaita Zone. Participants were selected using a systematic sampling method, and data was collected through structured questionnaires administered via interviews. The collected data was checked for completeness, coded, and entered into EpiData version 4.6. Analysis was conducted using the social science statistical package. Descriptive statistics were used to summarize the data, and results were presented through narratives, tables, and figures. Binary logistic regression analysis was employed to identify explanatory variables associated with safe infant sleep position practices. A p-value of ≤0.05 was considered statistically significant. Results A total of 569 study participants were included in this study with a response rate of 99.1%. The safe infant sleeping position practice (back to sleep) in this study was 42.7% [95% CI (38.6%, 46.8)]. Maternal occupation, parity, source information about sleep position, and good knowledge of safe sleep position practice were significantly associated by (AOR = 3.49; 95% CI (1.81, 6.76)), (AOR = 0.39; 95% CI (0.21, 0.74)), (AOR = 4.64; 95% CI (1.77, 12.18)), and (AOR = 2.04; 95% CI (1.22, 3.40)) respectively. Conclusion The study found that over half of participants did not practice safe infant sleeping positions. Factors such as maternal occupation, parity, information sources, and knowledge significantly influenced safe sleep practices. Targeted health education—particularly through antenatal and postnatal care services, as well as community-based awareness campaigns—is recommended to improve maternal knowledge and reduce sleep-related infant deaths.